Enhanced Salt Removal by Unipolar Ion Conduction in Ion Concentration Polarization Desalination - Kwak, Rhokyun; Van Sang Pham; Kim, Bumjoo; Chen, Lan; Han, Jongyoon (NATURE PUBLISHING GROUP, 2016)
Chloride ion, the majority salt in nature, is similar to 52% faster than sodium ion (DNa+ = 1.33, DCl- = 2.03[10(-9)m(2)s(-1)]). Yet, current electrochemical desalination technologies (e.g. electrodialysis) rely on bipolar ion conduction, removing one pair of the cation and the anion simultaneously. Here, we demonstrate that novel ion concentration polarization desalination can enhance salt removal under a given current by implementing unipolar ion conduction: conducting only cations (or anions) with the unipolar ion exchange membrane stack. Combining theoretical analysis, experiment, and numerical modeling, we elucidate that this enhanced salt removal can shift current utilization (ratio between desalted ions and ions conducted through electrodes) and corresponding energy efficiency by the factor similar to(D- - D+)/(D- + D+). Specifically for desalting NaCl, this enhancement of unipolar cation conduction saves power consumption by similar to 50% in overlimiting regime, compared with conventional electrodialysis. Recognizing and utilizing differences between unipolar and bipolar ion conductions have significant implications not only on electromembrane desalination, but also energy harvesting applications (e.g. reverse electrodialysis).
Keywords: EXCHANGE MEMBRANE; SEAWATER DESALINATION; REVERSE ELECTRODIALYSIS; OVERLIMITING CURRENT; TRANSPORT PHENOMENA; SHALE GAS; WATER; FUTURE; ELECTROCONVECTION; TECHNOLOGY